AN IMPROVED METHOD FOR THE ISOLATION OF ARTEMISININ FROM ANNUAL WORMWOOD (ARTEMISIA ANNUA L.) GROWING IN UZBEKISTAN (Scientific journal of the Fergana State University, 2023)
The chemical composition of representatives of the plant Artemisia annua L. in different geographical regions, in particular the amount of artemisinin, was studied. However, the chemical composition of its representatives growing in Uzbekistan has not been studied. The aim of this study was to isolate and quantify artemisinin from the plant Artemisia annua L. in Uzbekistan, especially in the Ferghana Valley.The extraction of artemisinin from the plant Artemisia annua L. in organic solvents, thin layer and column chromatography, IR, and mass spectrometry were used to determine the physicochemical parameters, chemical composition, and structure of the isolated substance.Isolation of artemisinin from the plant Artemisia annua L., growing in the Ferghana Valley, was achieved by 1.2-1.5% by replacing organic solvents. The extraction process with petroleum ether was carried out at different times. It was found that the yield did not change significantly when the extraction time exceeded 2 days. When analyzing the IR and mass spectra of the obtained substance, it was noticed that the data corresponds to the structure of artemisinin.For the first time, the biologically active substance artemisinin was isolated from the plant Artemisia annua L. growing in the Ferghana Valley in Uzbekistan. Extraction and purification methods have been improved, and the overall yield has been increased to 1.5%.